Memory cueing during sleep modifies the interpretation of ambiguous scenes in adolescents and adults. (February 2016) - Groch, Sabine; McMakin, Dana; Guggenbühl, Patrick; Rasch, Björn; Huber, Reto; Wilhelm, Ines
Abstract: The individual tendency to interpret ambiguous situations negatively is associated with mental disorders. Interpretation biases are already evident during adolescence and due to the greater plasticity of the developing brain it may be easier to change biases during this time. We investigated in healthy adolescents and adults whether stabilizing memories of positive or negative scenes modulates the later interpretation of similar scenes. In the evening, participants learnt associations between ambiguous pictures and words that disambiguate the valence of the pictures in a positive or negative direction. Half of the words were acoustically presented (i.e. cued) during post-learning sleep which is known to benefit memory consolidation by inducing reactivation of learned information. Cued compared to un-cued stimuli were remembered better the next morning. Importantly, cueing positively disambiguated pictures resulted in more positive interpretations whereas cueing negatively disambiguated pictures led to less positive interpretations of new ambiguous pictures with similar contents the next morning. These effects were not modulated by participants' age indicating that memory cueing was as efficient in adolescents as in adults. Our findings suggest that memory cueing during sleep can modify interpretation biases by benefitting memory stabilization and generalization. Implications for clinical settings are discussed.